Depression Illness in Patients with Primary Hypothyroidism Presenting to Endocrine Clinic - Khalid Usman, Sandeep Kumar Kalra, Samia Sarwar, Tahir Ghaffar, Zulquernain Ahmed Zoak, Tahir Mukhtar Sayed (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Depression is associated with hypothyroidism. Somatostatin and serotonin are known to influence the hypothalamus-pituitary-thyroid axis, resulting in depression in hypothyroid patients. Neurological symptoms such as behavioral disturbances, anxiety, and depression can be associated with thyroid hormone deficiency. The present study aimed to evaluate the depression illness in primary hypothyroidism patients presented to endocrine clinics. Patients and Methods: This descriptive cross-sectional study was carried out on 124 primary hypothyroidism patients presented to the endocrine clinic of Hayatabad Medical Complex, Peshawar during the period from February 2022 to January 2023. Patients of either gender aged >17 years and diagnosed with hypothyroidism based on T3 or T4 lower level (<1.71 pg/mL or T4 <0.7 ng/dL), higher TSH level (>4.94 uIU/mL), and TSH lower levels (<0.35 uIU/mL) were enrolled. Besides obtaining sociodemographic information, status of thyroid function status, and depression associated factors were noted. Patient Health Questionnaire (PHQ-9) was used for screening the depression among hypothyroidism patients. Moreover, the laboratory results were obtained from the patient’s medical records. SPSS version 27 was used for descriptive statistics. Results: The overall mean age was 40.16 ± 10.52 years with an age range from 18 to 70 years. There were 115 (92.7%) females and 9 (6.3%) male. About 8.2% of patients were illiterate. There were 86.7% (n=85) married. The prevalence of varying degree depression illness was 36.7% (n=36). Fatigue, hair loss, memory problem, and gland enlargement were the most prevalent depression associated symptoms. The incidence of normal, low, and elevated TSH levels were 56.1% (n=55), 7 (7.1%), and 36.8% (n=36) respectively. The most common symptoms of hypothyroidism were fatigue and reproductive issues, followed by hair loss, weight gain, thyroid gland enlargement, and cognitive difficulties. The incidence of mild, moderate, moderately severe, and severe depression was 39.8% (n=39), 12.2% (n=12), 20.4% (n=20), and 5.1% (n=5) respectively. Among hypothyroid patients, the prevalence of most stressful issues such as family, social, emotional issues, and stressful life conditions were 29 (29.6%), 22 (22.4%), 18 (18.4%), and 62 (63.3%) respectively. Conclusion: The present study concluded that hypothyroid patients are more likely to suffer from depression and outlined the symptoms most commonly associated with depression. The incidence of depression in hypothyroid patients was 36.7%. Pregnancy, economic problems, educational problems, emotional problems, and social problems were the most common stressful situations among hypothyroid people. Patients with hypothyroidism are inclined to depression regardless of their TSH level or other risk factors such as socioeconomic problems. Keywords: Depression, Primary hypothyroidism, Treatment-resistance depression, Patient Health Questionnaire-9